Spain : Oversight and Supervision of Financial Market Infrastructures Technical Note. (IMF Staff Country Reports; Country Report, 2012)
This technical note focuses on financial market infrastructures (FMIs) in Spain. The way Spanish authorities supervise and oversee FMIs is an essential issue in promoting and maintaining domestic financial stability. Although systemically important payments systems are European or international based, there are currently four domestic securities settlement systems and three domestic central counterparties in Spain. Overall, authorities' responsibilities with respect to FMIs are clearly defined in the law, but further transparency on Banco de Espana's (BdE) responsibilities with respect to FMIs other than payments systems is recommended.